Perceptions of electronic cigarette between current and former users: Findings from the national electronic cigarette survey among Malaysian adults 2016 - Mohd Yusoff, Muhammad Fadhli; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Ling, Jane Miaw Yn; Rodzlan Hasani, Wan Shakira; Tee, Guat Hiong; Lim, Kuang Hock (Malaysian Medical Association (MMA), 2017)
Introduction: The use of electronic cigarettes (e-cigarettes) has increased rapidly around the world. In Malaysia, apart from tobacco smoking, the use of e-cigarette has emerged as an alternative habit among the population. Among the reasons given by the users are to help them to quit or to cut down tobacco smoking. The objective of this study is to identify differences in the perceptions about e-cigarette between the former and the current users. Method: A nationwide household survey was conducted in 2016 to study the use of electronic cigarettes among Malaysian adults. A multistage stratified sampling method was used and about 3500 Living Quarters (LQs) were sampled. All eligible respondents aged 18 years and above were included in the survey. Respondents were asked on e-cigarette use and their perceptions about e-cigarettes. Analysis were done to identify differences in the perceptions about e-cigarette between the former and the current e-cigarette users. Results: A total of 4,288 adults participated in the survey, where 110 and 289 were identified as current and former e-cigarette users respectively. Compared to the current e-cigarette users, the former e-cigarette users were more likely to disagree that e-cigarette helps people to quit tobacco smoking (OR: 2.6), helps people to maintain cigarette abstinence (OR: 2.7), helps people to cut down tobacco smoking (OR: 2.5), is less harmful to health of the user compared to tobacco smoking (OR: 2.6), is less addictive than tobacco cigarette (OR: 2.6), the vapour is less harmful to others compared to tobacco smoke (OR: 2.4) should be allowed in places where smoking is banned (OR: 2.5) and should be regulated rather than banned completely (OR: 1.8). Conclusion: Significant differences in the perceptions about e-cigarette were observed between the former and the current e-cigarette users. Continuous health education should be given to change the perceptions about e-cigarette among the users.